Fenomena Ibadah Online Dari Perspektif Teologi - Sampouw, Fransiska Angela; Andrian, Tonny (JURNAL KADESI, 2025)
The development of digital technology has changed the way churches understand and practise worship, especially since the COVID-19 pandemic accelerated the shift to online forms. This article theologically examines the phenomenon of online worship through a literature study focusing on the concepts of God's presence, sacramentality, and the community of faith. Using a theological hermeneutical approach, this study interprets the meaning of digital worship based on the works of theologians such as Gunawan, Thompson, Bauer, Tück, Boersma, and others. The results of the study show that God's presence is not limited by physical space but is mediated by the faith of believers united in the name of Christ. The concept of real presence is reinterpreted as a spiritual experience that can occur in digital space as long as it is based on faith awareness and the work of the Holy Spirit. Meanwhile, the issue of sacramentality raises tension between the incarnational understanding that emphasises physical presence and the spiritual approach that sees sacraments as symbols of faith that can be interpreted online. On the other hand, faith communities in the virtual era have developed into digital koinonia, a fellowship connected spiritually through technology, without negating the importance of physical interaction. This study affirms that online worship is not merely a technological adaptation, but an opportunity for the church to broaden its theological understanding of presence, fellowship, and mission in the digital world. With contextual theological reflection, the church can make digital space a place for the growth of faith, ministry, and witness to Christ in modern society.